2017
DOI: 10.1097/meg.0000000000000986
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of branched-chain amino acid supplementation and walking exercise for preventing sarcopenia in patients with liver cirrhosis

Abstract: BCAA supplementation and walking exercise were found to be effective and easily implemented for improving muscle volume and strength in liver cirrhosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
98
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 19 publications
3
98
0
6
Order By: Relevance
“…In the present analysis, a finger‐circle test result other than Bigger in male patients and Smaller in female patients predicted early occurrence of MA. Daily physical activity has been reported to be lower in CLD patients as compared with healthy subjects . To confirm the relationships among total muscle volume or area of L3, maximum calf circumference, and level of daily physical activity, an additional study is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis, a finger‐circle test result other than Bigger in male patients and Smaller in female patients predicted early occurrence of MA. Daily physical activity has been reported to be lower in CLD patients as compared with healthy subjects . To confirm the relationships among total muscle volume or area of L3, maximum calf circumference, and level of daily physical activity, an additional study is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these patients should undergo intensive exercise and receive nutritional support. It was reported that walking exercise and branched chain amino acid supplementation contributed to improvement of skeletal muscle volume and strength in liver cirrhosis patients . The degree of skeletal muscle attenuation may have utility in identifying patients with muscle wasting and impaired nutritional status who may benefit from intensive nutritional and exercise support.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, prevention of progression of MVL and muscle function decline is important in the early stages of CLD. A few reports for intervention with nutritional guidance and exercise for improvement of muscle strength or prevention of decline and MVL have been reported . To improve the prognosis and quality of life in CLD patients with and without HCC, establishment of nutritional and exercise programs is needed.…”
Section: Discussionmentioning
confidence: 99%